Soil cyanobacterial and microalgal diversity in dry mountains of Ladakh, NW Himalaya, as related to site, altitude, and vegetation - Reháková, Klára; Chlumská, Zuzana; Doležal, Jiří (Microbial ecology, 2011)
Although phototrophic microbial communities are important components of soils in arid and semi-arid ecosystems around the world, the knowledge of their taxonomic composition and dependency on soil chemistry and vegetation is still fragmentary. We studied the abundance and the diversity of cyanobacteria and eukaryotic microalgae along altitudinal gradients (3,700-5,970 m) at four sites in the dry mountains of Ladakh (Little Tibet, Zanskar Mountains, and Eastern Karakoram), using epifluorescence. The effects of environmental factors (altitude, mountain range, and vegetation type) on soil physico-chemical parameters (pH; texture; organic matter, nitrogen, ammonia, and phosphorus contents; and concentration of chlorophylls and carotenoids) and on the composition and biovolume of phototrophs were tested by multivariate redundancy analysis and variance partitioning. Phototrophs were identified in all collected samples, and phototroph biovolume ranged from 0.08 to 0.32 mm(3) g(-1) dry weight. The dominant component was cyanobacteria, which represented 70.9% to 98.6% of the biovolume. Cyanobacterial species richness was low in that only 28 morphotypes were detected. The biovolume of Oscillatoriales consisted mainly of Phormidium spp. and Microcoleus vaginatus. The environmental factors accounted for 43.8% of the total variability in microbial and soil data, 20.6% of which was explained solely by mountain range, 7.0% by altitude, and 8.4% by vegetation type. Oscillatoriales prevailed in alpine meadows (which had relatively high organic matter and fine soil texture), while Nostocales dominated in the subnival zone and screes. Eukaryotic microalgae together with cyanobacteria in the order Chroococcales were mostly present in the subnival zone. We conclude that the high elevation, semiarid, and arid soils in Ladakh are suitable habitats for microbial phototrophic communities and that the differences in these communities are associated with site, altitude, and vegetation type.
Keywords: Biota; Altitude; Tibet; společenstvo; Phototrophic Processes; Soil; Cyanobacteria; Soil Microbiology; fluorescenční mikroskopie; nadmořská výška; sinice; půda; mikrořasy; Chlorophyll; Microscopy, Fluorescence; půdní mikrobiologie; chlorofyl; Microalgae; fototrofní procesy; Multivariate Analysis; multivariační analýza